Caracterización clínica y de laboratorio en el diagnóstico de dengue en el Ecuador - Grefa Tapuy, Melisa Liseth (2021)
This research was carried out under the bibliographic review modality, which aims to collect updated bibliographic information on the clinical and laboratory characterization in the diagnosis of dengue in Ecuador. The methodology applied was descriptive, documentary design, cross-sectional, and retrospective. Despite the scant information, data was collected through the Guide to care for dengue patients in the Americas region, present on the MSP's official website. The current investigation contains justification, work methodology, development, and conclusions, with general concepts about dengue, classification of the disease, patient management, and laboratory tests applied in the country. For the study population, information was collected through primary and secondary sources. For the sampling, 64 publications were chosen through search engines for scientific journals and distributed as follows: scielo-6, Redalyc-4, PubMed-6, Mendeley- 8, Dialnet-2, medigraphic-2, NCBI-9, Science Direct-3, BMC-1, INSPILIP-1 including web pages (1-OMS, 2-OPS, 5-MSP, 1-Hindawi, 1- KJCL), books in pdf 11. The results obtained in this bibliographical review show that dengue's clinical characterization is a symptom's variety. Presenting organ involvement, bleeding, or even patient mortality corroborated by several authors from different countries. The tests applied in the country are Elisa with the capture of NS1 and detection of antibodies through a qualitative serological test, ELISA with the capture of IgM and IgG, RT-PCR.